Effect of calcination temperature on the microstructure, composition and properties of nanometer agglomerated 8YSZ powders for plasma spray-physical vapor deposition (PS-PVD) and coatings thereof. Issue 12 (15th June 2021) - Li, Xin; Deng, Chunming; Niu, Shaopeng; Wang, Chao; Sun, Yaoning; Su, Weiming; Liu, Min; Deng, Ziqian; Zhang, Xiaofeng
Abstract: Homemade nano-agglomerated powders 8YSZ powders for PS-PVD were prepared by the spray drying, then calcination processes at four different temperatures (500 °C, 700 °C, 900 °C and 1100 °C) were carried out on the spray-dried powders. Checked by laser particle sizer, scanning electron microscope (SEM) and X-ray diffraction (XRD), the physical properties, microstructure and phase constitutions of the calcined powders were investigated. The results show that the size of powders calcined at 500 °C is increased relative to the spray-dried powder, whereas the powders calcined at 700 °C, 900 °C and 1100 °C possess smaller size. The binding force of the primary particles tend to rise with the increase of calcination temperature. When the temperature was up to 900 °C and above, it was found that the sintering neck indicating with strong binding was formed between the primary particles. In parallel, the powders underwent an m-ZrO2 to t-ZrO2 transition as the calcination temperature rose. It is also found that the PS-PVD prepared coatings which were obtained by using the above powders undergo a transformation from a feather-like to a dense laminate structure as the calcination temperature rises. It is noteworthy that the coating obtained by the powders calcined at 700 °C have a special three-layer composite structure of near dense surface layer, columnar intermediate layer and dense sub-layer. The composite structural coating has excellent adhesion and thermal shock resistance, with a bonding strength of 81MPa and no major spalling when water quenched 100 cycles at 1100 °C.